The effect of poor adherence to treatment of people living with HIV/AIDS - Jeneke, Johannes Marthinus (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MPhil (Industrial Psychology. Africa Centre for HIV/AIDS Management))--University of Stellenbosch, 2011.